Sinopsis en Idioma Inglés - Reflexión Política, Revista (UNAB, 2020)
Resumen VENEzUELA , PHENOMENOLOGY OF A CRISISEnrique Neira FernándezThe author shows in a first reflection the historical conjunction presented in the crisis of social processes and structures in Venezuela. This crisis presents processes simultaneously derived from the important which means that it has become a country with great petrol riche which have provoked the modernization and urbanization in cities, aided by advanced technology and science. The main manifestations of this crisis are the lack of a political class, the lack of a new generation of leaders and the lack of institutionalism which has left society without clear definition to aid development. Becouse of these things, the vices of the Venezuelan are, e.g. lack of social responsibility, civil cowardliness and an indifference to society.